Myocarditis Associated with Immune Checkpoint Inhibitors: An Expert Consensus on Data Gaps and a Call to Action. (25th May 2018) - Neilan, Tomas G.; Rothenberg, Mace L.; Amiri‐Kordestani, Laleh; Sullivan, Ryan J.; Steingart, Richard M.; Gregory, William; Hariharan, Subramanian; Hammad, Tarek A.; Lindenfeld, JoAnn; Murphy, Martin J.; Moslehi, Javid J.; ,
Abstract : Immune checkpoint inhibitors (ICIs) have transformed the treatment landscape for cancer. Due to the mechanism of action of ICIs, inflammatory reactions against normal tissue were an anticipated side effect of these agents; these immune‐related adverse events have been documented and are typically low grade and manageable. Myocarditis has emerged as an uncommon but potentially life‐threatening adverse reaction in patients treated with ICIs. Assessment and characterization of ICI‐associated myocarditis is challenging because of its low incidence and protean manifestations. Nevertheless, the seriousness of ICI‐associated myocarditis justifies a coordinated effort to increase awareness of this syndrome, identify patients who may be at risk, and enable early diagnosis and appropriate treatment. The "Checkpoint Inhibitor Safety Working Group, " a multidisciplinary committee of academic, industry, and regulatory partners, convened at a workshop hosted by Project Data Sphere, LLC, on December 15, 2017. This meeting aimed to evaluate the current information on ICI‐associated myocarditis, determine methods to collect and share data on this adverse reaction, and establish task forces to close the identified knowledge gaps. In this report, we summarize the workshop findings and proposed steps to address the impact of ICI‐associated myocarditis in patients with cancer. Abstract : Immune checkpoint inhibitors are a class of drugs that trigger the immune system to recognize and fight cancer cells; however, related immune‐related adverse events are a challenge. This commentary describes a workshop convened by Project Data Sphere to determine best approaches in the treatment of myocarditis, with the goal of minimizing the risk of this adverse reaction in patients with cancer who are treated with immune checkpoint inhibitors.